Comparative Estimation of Ecological Rent in Absheron and Sheki-Zagatala Economic Regions of Azerbaijan Republic - Ahmadov, Nasimi (European Journal of Sustainable Development, 2017)
The article studies the peculiarities of development of the regions in Azerbaijan economy and analyzes some indicators characterizing the current state of economic development and usage of natural resources in Absheron and Sheki-Zagatala economic regions of the country. The ecological potential of the country and its economic regions has significant importance in increasing of the usage of natural resources and in ensuring the sustainable development. By taking into consideration this the essence of ecological rent is explained and for the first time its quantity is determined comparatively in Absheron and Sheki-Zagatala economic regions of Azerbaijan by using N.N. Klyuev method of determining the "ecological tax". Keywords: ecological rent, sustainable development, oil and natural gas production, Azerbaijan economy, Absheron region, Sheki-Zagatala region, technological and physiological energy consumption, biological productivity, land areas, forests, arable